Dampak Pemanfaatan Media Canva terhadap Peningkatan Kreativitas Belajar Siswa Ekonomi Kelas XI di SMAN 1 Tulungagung Tahun 2024/2025 - Wisnu Wahyu Widayat; Sulastri Rini Rindrayani (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study was to understand the effect of using Canva-based learning media on the creativity of eleventh-grade students in economics. The background of this study stems from the low level of student learning creativity caused by the minimal use of innovative and engaging media in the learning process. Creativity is an important aspect in economics learning because it encourages students to think critically, create solutions, and understand abstract concepts more contextually. Static and monotonous learning media such as blackboards and textbooks often do not sufficiently stimulate student interest and participation. Therefore, a more interactive and visual approach is needed, one of which is using Canva. Canva is an online graphic design platform that allows teachers and students to easily create presentations, infographics, and other visual materials. Using Canva in learning can provide a more enjoyable learning experience and motivate students to be actively involved. This study used a quantitative method with a one-group pretest-posttest pre-experimental design. Data analysis was carried out by comparing creativity scores before and after treatment. Student creativity was measured using a test instrument that included aspects of fluency, flexibility, originality, and elaboration. The study subjects were 34 11th-grade students at SMAN 1 Tulungagung. The results showed a significant difference in scores between the pretest and posttest results, indicating that the use of Canva-based learning media had a positive impact on increasing student creativity. Students became more active in expressing ideas, more daring to experiment with concepts, and better able to present learning outcomes visually and attractively. These findings support constructivism theory, which states that effective learning occurs when students actively construct knowledge through meaningful experiences.